The priorities of the Polish presidency of the Council of the European Union – the circumstances of their selection and implementation - Przybylska-Maszner, Beata; Jańczak, Jarosław (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The paper discusses the Polish presidency of the EU Council in terms of its priorities. It analyzes the circumstances of their formulation, selection and implementation. The authors answer the question of what influenced the selection of Poland’s priorities and what selection mechanisms were applied. Additionally, they examine how the national agenda was ‘concealed’ in Community rhetoric. Thus, the analytical part discusses the political and legal path that determined the priorities. The EU agenda, Polish ambitions and the context of the trio is also presented. The paper concludes with the authors’ assessment of the implementation of the priorities.